Work Status of Individuals with Advanced Cancer. (September 2014) - Terhaar, Abigail; Lee, Ju-Whei; Tevaarwerk, Amye; Sesto, Mary; Wiegmann, Douglas; Fisch, Michael
Lengthening survival times for advanced cancer patients emphasizes the importance of continuing to work after diagnosis. Information and tools are necessary to help these individuals remain working. Before we can develop interventions, we must understand how advanced cancer affects employment. We analyzed Eastern Cooperative Oncology Group's (ECOG) "Symptom Outcomes and Practice Patterns (SOAPP)" study to investigate what factors were associated with employment of 680 advanced cancer patients. Univariable and multivariable logistic regression analyses were conducted to compare patients identified as stably working (Group A) to patients no longer working (Group B). Improving ECOG performance status, race/ethnicity, receiving hormonal treatment, and decreasing symptom interference were significantly associated with continuing to work. Human factors engineers (HFEs) can help create strategies to mitigate some physical and cognitive workloads that result in work interference. The HFE's role should increase as the number of advanced cancer patients working rises.